Performance of the LHCb RICH detectors during LHC Run 2. (1st July 2022) - Calabrese, R.; Fiorini, M.; Luppi, E.; Minzoni, L.; Slazyk, I.; Tomassetti, L.; Bartolini, M.; Cardinale, R.; Fontanelli, F.; Petrolini, A.; Pistone, A.; Calvi, M.; et al.
Abstract: The performance of the ring-imaging Cherenkov detectors at the LHCb experiment is determined during the LHC Run 2 period between 2015 and 2018. The stability of the Cherenkov angle resolution and number of detected photons with time and running conditions is measured. The particle identification performance is evaluated with data and found to satisfy the requirements of the physics programme.